Paolo Zermani. Scuola per l’Europa a Parma - Uccelli, Vittorio (Firenze Architettura, 2021)
Paolo Zermani’s School for Europe (Scuola per l’Europa) lies on the Valley of the Po as a place for recomposing the territory, aware of the fact that a world converges on it, of which it is the centre. Walking along its porticoed streets, so near the rows of mulberry trees and the irrigation canals that mark the boundary with the adjacent agricultural fields, it is possible to understand how it is the great themes of the Po Valley architecture that construct the body of this building.